Palliative care consultations in a tertiary hospital Emergency Department. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Cassel, J Brian; Luckholm, Laurie; Coyne, Patrick; Korshin, Timur
Abstract : Background: In the USA, our Palliative Care (PC) program is unique in its early intervention in the Emergency Department (ED). Aims: Our goals for this study were to (1) describe PC involvement in the ED at our hospital; (2) describe the typical reasons for PC involvement; and (3) describe what happened to patients following initial consultation. Methods: We analysed the 'tracking sheets' documenting PC consultations from the years 2006–2011 that occurred in the ED. For the years 2008–2011 we matched the consult data to hospital billing and administrative databases for the ED visit and/or eventual hospitalisation. Results: Since 2006, 429 patients received a palliative care consultation during an ED visit. This increased from 36 in 2006 to more than 90 in each of the past two years. Reasons for consultation included pain (52%), other symptoms (54%), and goals of care (54%); 17% were solely for pain, 11% were solely for other symptoms and 21% were solely for goals of care. Hospital data were available for 252 cases seen since July 2008. Six died in the ED, 31 were released from the ED, twelve were held in the hospital as 'observation' cases and 203 (81%) were admitted. Fifty-one (25%) of those hospitalisations ended in death and another 25% ended in discharge to hospice. 162 (80%) were admitted to the PC Unit, for an average of 3.9 days, almost all directly from the ED. Only seven were admitted into intensive care units (ICUs), for an average of 3 days; only one died in the intensive care unit (ICU). Conclusions: Compared to inpatient consultations for our PC program, consultations in the ED have a higher frequency of goals of care reasons, and lower for pain-only or symptoms-only. For those hospitalised following consultation, length of stay and ICU utilisation are quite low by US standards.